Algebra-Gleichungen-Exponentialgleichungen


  • $a b^{(cx+d)}+f=0 $
    1 2 3 4 5 6
    $a e^{(cx+d)}+f=0 $
    1 2 3 4

Beispiel Nr: 04
$ \text{Gegeben:}a b^{(cx+d)}+f=0 \\ \text{Basis: }b \\ \\ \text{Gesucht:} \text{Lösung der Gleichung} \\ \\ a b^{(cx+d)}+f=0 \\ \textbf{Gegeben:} \\ a=-2 \qquad b=3 \qquad c=2 \qquad d=1 \qquad f=10 \\ \\ \textbf{Rechnung:} \\ -2 \cdot 3^{(2x+1)}+10 =0 \\ -2 \cdot 3^{(2x+1)}+10=0 \qquad /-10 \\ -2 \cdot 3^{(2x+1)}=-10 \qquad /:-2 \\ 3^{(2x+1)}=5 \qquad /\log_3 \\ 2x+1=\log_3 \left(5 \right) \qquad / -1 \qquad / :2 \\ x=0,232 $